Evaluation of a simple low-cost intervention to empower people with CKD to reduce their dietary salt intake: OxCKD1, a multicenter randomized controlled trial - O'Callaghan, CA; Camidge, C; Thomas, R; Reschen, ME; Maycock, AJ; Lasserson, DS; Fox, RA; Thomas, NPB; Shine, B; James, T (Wolters Kluwer, 2023)
Key Points •A randomized controlled trial demonstrates that a simple and cheap 1-month intervention empowers people with CKD to lower their dietary salt intake. •The effect of the intervention persisted after the intervention finished. Background To evaluate the efficacy of a simple low-cost intervention to empower people with CKD to reduce their dietary salt intake. Methods A randomized controlled trial in primary and secondary care comparing the OxSalt care bundle intervention versus standard care for 1 month. Participants were people with CKD and an eGFR >20 ml/min per 1.73 m2 and were recruited from primary and secondary care. The primary outcome was a reduction in dietary salt intake, as assessed by 24-hour urinary sodium excretion, after 1 month of the intervention. Results Two hundred and one participants were recruited. Dietary salt intake, as assessed from 24-hour urine sodium excretion, fell by 1.9 (±2.9) g/d in the intervention group compared with 0.4 (±2.7) g/d in the control group (P < 0.001). Salt intake was still reduced to a lesser extent over the following year in the intervention group. Conclusions A short, low-cost, easily delivered intervention empowers people with CKD to reduce their dietary salt intake. Trial registration ClinicalTrials.gov NCT01552317.